Retrospective study of relationship between vastus medialis volume on SPECT-CT and outcome of unilateral total knee arthroplasty. Issue 1 (8th January 2021) - Kim, Hyeong Jik; Park, Hyung Jun; Oh, Jong Byung; Chang, Moon Jong; Kang, Seung-Baik; Kim, Yu Kyeong; Oh, So Hee; Chang, Chong Bum
Abstract : Abstract: Although the importance of quadriceps femoris function was reported previously, little is known about volume-related factors and their effects on clinical outcomes after total knee arthroplasty (TKA). We sought to determine whether there was a bilateral difference in vastus medialis muscle volume measured on single-photon emission computed tomography–computed tomography (SPECT-CT) in patients who underwent unilateral TKA. We also aimed to determine whether vastus medialis volume was related to osteoarthritis (OA) severity or scintigraphic uptake degree around the knee joint on SPECT-CT. And finally, we attempted to investigate the factors, such as vastus medialis volume and scintigraphic uptake degree, associated with the functional outcomes of TKA. This retrospective study included 50 patients (41 female, 9 male) undergone unilateral TKA due to primary OA. The maximal cross-sectional area of the vastus medialis was measured on axial SPECT-CT images. Scintigraphic uptake degrees and Kellgren-Lawrence (K-L) grade at the tibiofemoral joints were assessed. We compared maximal cross-sectional area of the vastus medialis on SPECT-CT for difference of bilateral lower limbs. We also analyzed the relationship between volume of vastus medialis and scintigraphic uptake measured on SPECT-CT and the severity of OA on conventional radiographs. The clinical outcomes were evaluated using the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) index at baseline and at 1 and 2 years after surgery. The relationship between preoperative muscle volume and scintigraphic uptake on SPECT-CT and WOMAC index was analyzed. The amount of muscle volume measured on SPECT-CT was smaller in operated limb in patients who underwent unilateral TKA. Preoperative vastus medialis muscle volume was not related to preoperative OA severity measured on conventional radiographs and scintigraphic uptake on SPECT-CT. However, a decreased vastus medialis muscle volume was related to worse clinical outcomes after TKA ( P  = .045), whereas the degree of scintigraphic uptake on SPECT-CT was not associated with postoperative clinical outcomes. Muscle volume of vastus medialis was decreased in the operated knee than in the nonoperated knee, and that was correlated with worse postoperative results. Even if the preoperative volume of vastus medialis were not related to OA severity on conventional radiographs and scintigraphic uptake on SPECT-CT, preservation and improvement of the muscle mass of the knee undergoing TKA is important.